Are we approaching a post-monolithic era? - Urban, Jiří (Journal of separation science, 2020)
Thirty years after their introduction, monolithic stationary phases are an important member of chromatographic phases. When compared to conventional particulate materials, the continuous internal structure of both inorganic silica and organic polymer monoliths allows some hydrodynamic and analytical possibilities that are not provided by conventional particulate stationary phases. Polymer-based monolithic stationary phases offer simple preparation and straightforward surface modification, which makes them very versatile materials that are applicable, for example, as chromatographic stationary phases, sample enrichment units, enzymatic reactors, and external trigger-responding materials. On the other hand, current polymer monoliths cannot compete with efficiency provided by superficially porous and sub 2 µm particles. In this highlight article, I take advantage of the 30th anniversary of their introduction to discuss several concerns related to polymer-based monolithic stationary phases. Particularly, I focus on preparation repeatability, porous properties, swelling of the polymers in organic solvents, column efficiency for small molecules, and heterogeneity of dominant flow-through pores. In the end, I offer three possible approaches on how to overcome drawbacks related to stationary phases heterogeneity to further increase the applicability of polymer-based monolithic stationary phases.
Keywords: stationary phases; polymer monoliths; heterogeneity; gel porosity